Mpox: Transmission Insights, Pathogenesis, and Emerging Therapeutics (Early view) - Diana Mendonça, Ryan V. Labana, Abolghasem Siyadatpanah, Sónia M.R. Oliveira, Chooi-Ling Lim, Shanmuga S Sundar, Sunil Kayesth, Karma G. Dolma, Christophe Wiart, Maria de Lourdes Pereira and Veeranoot Nissapatorn, (Tropical Life Sciences Research, 2026)
Introduction: Mpox is a re-emerging zoonotic disease that has experienced a global resurgence. Contributing factors include discontinuing smallpox vaccination and climate change-related events, such as species migration and the urbanization of forest areas. Methods: A comprehensive analysis of related literature was conducted. This literature review covers topics on the transmission routes of the monkeypox virus, infection control, diagnosis, treatment, and potential new technologies or ethnopharmaceuticals to inhibit infection. Results: This review paper is divided into four major parts: (1) transmission pathways: airborne and contact routes of respiratory pathogens, (2) mpox diagnosis: from clinical presentation to laboratory testing, (3) pathogenesis of mpox and interaction with other co-existing diseases, and (4) mpox prevention and treatment strategies. The last section is divided into subsections: vaccine, antivirals, and exploring alternative approaches against mpox. The alternative approaches cover topics on the application of nanotechnology and plant-based therapies. The paper concludes with a discussion of future directions for mpox. Conclusion: Research on mpox underscores the urgent need for improved diagnostics, treatment evaluation, and prevention strategies. The current outbreak highlights gaps in our understanding of the virus, particularly its transmission dynamics and the long-term efficacy of existing therapies. Advancing research into alternative treatments, such as nanotechnology and medicinal plants, alongside enhanced global surveillance and rapid response systems, will mitigate future outbreaks and improve public health outcomes.